ANALISIS TATA LETAK FASILITAS DENGAN MENGGUNAKAN METODE ACTIVITY RELATIONSHIP CHART PADA INDUSTRI MEBEL BAMBU KARYA MANUNGGAL YOGYAKARTA - Astuti, Marni; Poerwanto, Eko; Trianingsih, Agus (Institut Teknologi Dirgantara Adisutjipto, 2017)
Plant layout or facilities layout is to fix regulate facilities layout with consider material handling flow. In this research on Bamboo Furniture Industry Karya Manunggal Yogyakarta show less precisely placement of production facilities and flow material resulting in the total distances of material handling becomes long and induce the total cost of material handling becomes high.Improvement of facilities layout performed with qualitative methods ARC (Activity Relationship Chart). This matter do for obtain a new layout with minimum total distances of material handling and minimum total cost of material handling. In this research use POM QM Software for validating total distances of material handling.Analysis result and designing facilities layout is a new layout with Rectilinear Distance method, The initial movement distances is 1.922,9 m become 1.832,35 m or have a reduction distances 4,94 % from initial layout. While for the initial total cost of material handling is Rp 200.135,6 become Rp 199.745,9 or have a reduction cost 0,19% from initial layout. Existence a new layout based on ARC be expected on the production floor of Bamboo Furniture Industry Karya Manunggal Yogyakarta.